Effect of thermocycling aging on the flexural strength of feldspathic ceramic - Carvalho, Ronaldo Lúís Almeida de; kimpara, Estevão Tomomitsu; Bresciani, Eduardo; Valera, Márcia Carneiro; Melo, Renata Marques (Brazilian Dental Science, 2018)
Objective: The aim of the study was to evaluate the effect of aging through different thermocycling protocols on the flexural strength of a feldspathic ceramic. Material and Methods: Fifty ceramic bars, Vitablock Mark II (VITA), with dimensions of 18X4X2mm were prepared. The bars were randomly distributed to the groups (n = 10), which were defined according to the number of thermal cycles (TCy): G0 - no TCy; G500 - 500 cycles of TCy; G6000 - 6000 TCy; G10000 - 10000 TCy; G15000 - 15000 TCy. After aging, the specimens were subjected to the three point bending test in a universal testing machine (EMIC DL 1000), under 0.5mm/min speed and loading of 50kgf, until catastrophic failure. A sample of each group was evaluated for topographic morphology under Scanning Electron Microscopy. Results: For mechanical testing, the following mean values and standard deviation (MPa) were obtained: G0 (99.78 ± 5.07); G500 (101.64 ± 5.59); G6000 (98.13 ± 4.95); G10000 (91.77 ± 9.68); G15000 (101.51 ± 4.22). An analysis of variance by regression equation (p = 0.387) was performed, demonstrating a weak and non-significant correlation between flexural strength and number of thermal cycles. Conclusion: It can be concluded that aging in water solely by different numbers of temperature cycles did not influence on the flexural strength of a feldspathic ceramic. Keywords Material resistance; Aging; Ceramics.